ASEAN and its approach to forced migration issues. Issue 2 (17th February 2016) - Petcharamesree, Sriprapha
Abstract : The issue of forced migration has been a difficult challenge for ASEAN to address. Despite the number of international, regional and national frameworks in place, it is clear that within the international community, emigration is regarded as a right but immigration is seen as a matter of national sovereignty and security. Irregular migrants, especially migrant workers, asylum seekers and refugees, are not only forced to leave their own state but they are vulnerable to the whims of their host state, because they are considered to be secondary to citizens and national interests. The purpose of this article is to examine forced migration in the ASEAN context and how ASEAN member states have perceived and dealt with the issues so far. It also looks critically at how ASEAN as a group has been approaching forced migration and whether the establishment of the ASEAN human rights regime has contributed to changing ASEAN's approach to forced migration. ASEAN has some policies and frameworks in place for the protection of immigrants, including for those who are forced, but are assumed to be voluntary. Although ASEAN has a number of regional frameworks which could be applied to protect the rights of those forced to migrate, it is regrettable that the overall policies and laws on migration are left to the will of national governments which, in many ways, may not comply with international human rights standards. Moreover, while the existence of the ASEAN human rights regime is significant, there are no guarantees that it will lead to the adoption of a common regional approach to forced migration. The fact that ASEAN has been upholding very strong working principles – respect of state sovereignty, non-interference in the international affairs of member states, consultation and consensus – weakens the existing ASEAN human rights system. In addition, although ASEAN is one organisation, it is made up of ten member states, each driven by their prevailing national approach to the issues. A regional approach like the one applied two decades ago, would be difficult to reach now, as the member states do not yet see forced movements and forced migration as a 'crisis'. While ASEAN does react to issues, it is always reluctant to act before the issue becomes a 'crisis'. However, even if ASEAN reacts, it might not be in support of the interests of those who are forced to leave their country.